2021
DOI: 10.5937/jomb0-28846
|View full text |Cite
|
Sign up to set email alerts
|

Retinol binding protein 4 levels relate to the presence and severity of coronary artery disease

Abstract: Background: The prevous studies has showed that serum retinol binding protein 4 (RBP4) levels increased in metobolic disorders which are closely associated with cardiovascular dieases (CVD).  However the human studies investigating the role of RBP4 in CVD are conflicted. Therefore, we aimed to evaluate the relationship between RBP4 and the presence and the severity of coronary artery disease (CAD) in this study. Methods: 55 patients with presenting acute coronary syndrome (ACS) and 43 control subjects wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Peptidoglycan recognition protein 2 (PGLYRP2) is involved in immunomodulation and innate immunity, while the adenomatous polyposis coli (Apc) gene is crucial in development, negatively regulates Wnt signaling, and may be involved in angiogenesis [64][65][66][67][68][69]. Retinol binding protein 4 (RBP4) is linked to the severity of cardiovascular disorders, and complement factors are known to be associated with hemorrhagic stroke [35,[41][42][43][44][70][71][72][73]. These biomarkers may help in understanding and treating various vascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidoglycan recognition protein 2 (PGLYRP2) is involved in immunomodulation and innate immunity, while the adenomatous polyposis coli (Apc) gene is crucial in development, negatively regulates Wnt signaling, and may be involved in angiogenesis [64][65][66][67][68][69]. Retinol binding protein 4 (RBP4) is linked to the severity of cardiovascular disorders, and complement factors are known to be associated with hemorrhagic stroke [35,[41][42][43][44][70][71][72][73]. These biomarkers may help in understanding and treating various vascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Peptidoglycan recognition protein 2 (PGLYRP2) is involved in immunomodulation and innate immunity, while the adenomatous polyposis coli (Apc) gene is crucial in development, negatively regulates Wnt signaling, and may be involved in angiogenesis [90][91][92][93][94][95] . Retinol binding protein 4 (RBP4) is linked to the severity of cardiovascular disorders, and complement factors are known to be associated with hemorrhagic stroke 61,[67][68][69][70][96][97][98][99] . These biomarkers may help in understanding and treating various vascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survival analysis was conducted for AMI patients, and the results showed that AMI patients in high concentration group had a prominently shorter survival time than those in low concentration group. A large amount of extracellular visfatin can release numerous inflammatory factors, which causes the rupture of unstable atheromatous plaques, increases the incidence rate of adverse cardiovascular events in AMI patients and distinctly shortens the survival time of the patients [17] . Atrial fibrillation is currently one of the most common types of persistent arrhythmia in clinic, and PCI-induced atrial fibrillation is closely associated with AMI, whose risk can be reduced remarkably by administration with anticoagulants and antiplatelet agents [18] [19] .…”
Section: Discussionmentioning
confidence: 99%